Investigation of SARS-CoV-2 and gastrointestinal pathogens in a municipal wastewater treatment plant in Turkey - Topal, Murat; Toraman, Zülal Aşçı; Topal, E.ışıl Arslan; Süer, Ceren Sel; Öbek, Erdal (My University, 2021)
In this study, SARS-CoV-2 and gastrointestinal pathogens in a municipal wastewater treatment plant (MWWTP) in Elazığ (Turkey) were investigated. The gastrointestinal pathogen analyzes were performed in influent and effluent of MWWTP, and SARS-CoV-2 analyzes were performed in different treatment units. According to obtained analysis results, gastrointestinal pathogens (bacterial, viral, EPA, and stool parasites) were detected in influent of the MWWTP. Enterohemorragic/verotoxin-producing Ecsherichia coli, all viral agents causing gastroenteritis (except sapoviruses (Sapo)), human parechovirus (HPeV) and adenoviruses from EPA, and Giardia lamblia from stool parasites were detected in effluents of the MWWTP. When bacterial agents causing gastroenteritis, viral agents, EPA, and stool parasites were investigated in the effluent of MWWTP, only 1 agent out of 7, 4 agents out of 6,2 agents out of 3, and 1 agent out of 3 was detected as positive (+), respectively. SARS-CoV-2 could not be detected in the samples taken from each unit of the wastewater treatment plant. As a result, according to research findings, since pathogens are encountered in wastewater treatment plant effluents, it is necessary to have a disinfection system in the treatment plants and to monitor pathogens and SARS-CoV-2 continuously in order to protect environmental and human health.
Keywords: Gastrointestinal; pathogen